The role of innovative approaches in aesthetic vocal performance (Música Hodie, 2021)
Vocal art is a means of conveying the artistic content of a musical work through voice, sounds, words, and intonation. The key objective of the research is to study the role of innovative approaches required for the aesthetic vocal performance. The method of a sociological survey and the SWOT analysis were used to achieve the goal of the study. The study involved 60 students from the Shenyang Conservatory of Music. The role of new technologies in teaching singing was determined with the help of two methods: the methodology by Strelnikova and the methodology developed in the course of the study. It was found that an integrated approach to teaching vocal performance is more effective and allows learners to achieve great results. This is evidenced by the results of a sociological survey. The use of the methodology developed allowed 89% of the participants to obtain high results two months after the beginning of training while only 77% of students improved their performance through the application of the methodology by Strelnikova. This is due to the fact that the long-known technique is aimed exclusively at breath building, which is an integral part of singing, but it does not include other important elements. In addition, based on the SWOT analysis, strengths and weaknesses, as well as opportunities and threats were identified in the context of each method. The completeness of the data of the methodology developed has significant advantages for the aesthetic performance of songs. The results of the study will be useful for vocalists when building voices, as well as teachers when developing a curriculum.